2017
DOI: 10.1161/hypertensionaha.116.08312
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Trajectories From Childhood to Young Adulthood Associated With Cardiovascular Risk

Abstract: To identify subgroups of individuals with similar trajectories in blood pressure (BP) from childhood to young adulthood, and to determine the relationship of BP trajectories with carotid intima-media thickness (IMT) and left ventricular mass index (LVMI). BP was measured up to 16 times over a 23-year period in 683 participants from childhood to young adulthood. IMT and LVMI were measured in 551 participants and 546 participants respectively. Using latent class models, three trajectory groups in BP from childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 53 publications
3
91
0
4
Order By: Relevance
“…Despite the impressive risk reduction in the primary composite outcome in SPRINT (HR with intensive therapy 0.75 [95% CI 0.64‐0.89], P < .001), the mean SBP in the intensive treatment group was 121.4 mm Hg at 1 year and 121.5 mm Hg throughout the follow‐up period, suggesting that more than half of the patients failed to reach the SBP treatment target of <120 mm Hg. Furthermore, BP changes in response to medication intensification differ over time across individuals, and could affect their cardiovascular outcomes . Hence, we hypothesised that SBP trajectory in SPRINT is associated with the cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impressive risk reduction in the primary composite outcome in SPRINT (HR with intensive therapy 0.75 [95% CI 0.64‐0.89], P < .001), the mean SBP in the intensive treatment group was 121.4 mm Hg at 1 year and 121.5 mm Hg throughout the follow‐up period, suggesting that more than half of the patients failed to reach the SBP treatment target of <120 mm Hg. Furthermore, BP changes in response to medication intensification differ over time across individuals, and could affect their cardiovascular outcomes . Hence, we hypothesised that SBP trajectory in SPRINT is associated with the cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bold values in Table 2 Western countries. 9,12,13,15,24,25 Another form of BP changes is the visit-to-visit blood pressure variability, and studies have found that higher variability of BP or SBP is a powerful predictor of cardiovascular events independently of mean SBP or DBP, which has been more common in previous studies. 7,11,14,[26][27][28] A large longitudinal study of U.S. veterans found that greater long-term visit-to-visit SBP variability was associated with higher risk of subsequent stroke, independent of mean SBP, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have confirmed and reinforced the importance of BP change by different forms for stroke. Limited prospective studies in the form of longitudinal elevated or decreased BP trajectories at several time points have emphasized that increase in BP is a major risk factor for adverse outcomes of CVD (including stroke) in China or Western countries . Another form of BP changes is the visit‐to‐visit blood pressure variability, and studies have found that higher variability of BP or SBP is a powerful predictor of cardiovascular events independently of mean SBP or DBP, which has been more common in previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…BP trajectories) are associated with increased risk of cardiovascular disease. We recently observed that different BP trajectories exist in childhood with participants in the rapidly increasing group showing more target organ damage in young adulthood, adding yet another important piece of evidence in supporting the arguments for routine BP screening in childhood [31]. The underlying genetic factors determining the degree of BP rise over time might be different from those that determine initial BP levels.…”
Section: Using Improved Phenotyping: Hypertension Classificationmentioning
confidence: 99%